2017
DOI: 10.1371/journal.pone.0176964
|View full text |Cite
|
Sign up to set email alerts
|

Genome wide analysis of the evolution of Senecavirus A from swine clinical material and assembly yard environmental samples

Abstract: Senecavirus A (SVA), previously known as Seneca Valley virus, was first isolated in the United States in 2002. SVA was associated with porcine idiopathic vesicular disease in Canada and the USA in 2007 and 2012, respectively. Recent increase in SVA outbreaks resulting in neonatal mortality of piglets and/or vesicular lesions in sows in Brazil, the USA and Canada point to the necessity to study the pathogenicity and molecular epidemiology of the virus. Here, we report the analysis of the complete coding sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
39
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 31 publications
2
39
0
Order By: Relevance
“…Foreign animal disease investigations indicated that other vesicular viral pathogens, such as foot-and-mouth disease virus (FMDV), swine vesicular disease virus (SVDV), vesicular stomatitis virus (VSV), and vesicular exanthema of swine virus (VESV), were negative in these cases [10]. Subsequently, SVV detection was reported by other laboratories in the U.S. [11][12][13][14][15][16], China [17][18][19][20][21], Canada [22], Thailand [23], and Colombia [24]. Vesicular lesions were induced in pigs following experimental inoculation with the contemporary U.S. isolates of SVV [25,26], confirming that SVV is a vesicular viral pathogen.…”
Section: Introductionmentioning
confidence: 99%
“…Foreign animal disease investigations indicated that other vesicular viral pathogens, such as foot-and-mouth disease virus (FMDV), swine vesicular disease virus (SVDV), vesicular stomatitis virus (VSV), and vesicular exanthema of swine virus (VESV), were negative in these cases [10]. Subsequently, SVV detection was reported by other laboratories in the U.S. [11][12][13][14][15][16], China [17][18][19][20][21], Canada [22], Thailand [23], and Colombia [24]. Vesicular lesions were induced in pigs following experimental inoculation with the contemporary U.S. isolates of SVV [25,26], confirming that SVV is a vesicular viral pathogen.…”
Section: Introductionmentioning
confidence: 99%
“…Seneca Valley virus (SVV) was identified from a contaminated PER.C6 cell line in 2002 (Leme, Alfieri, & Alfieri, ; Segales, Barcellos, Alfieri, Burrough, & Marthaler, ), whereas SVV‐associated porcine idiopathic vesicular disease (PIVD) was reported until 2007 in Canada and 2010 in the United States (US) (Leme et al., ; Pasma, Davidson, & Shaw, ; Singh, Corner, Clark, Scherba, & Fredrickson, ). Since the PIVD outbreak in swine herds in Brazil (Leme et al., ), this disease had been reported in the United States (Zhang et al., ), Colombia (Sun, Vannucci, Knutson, Corzo, & Marthaler,), Thailand (Saeng‐Chuto, Rodtian, Temeeyasen, Wegner, & Nilubol, ), Canada (Xu et al., ) and China (Wu et al., ), suggesting a gradually increasing geographic distribution.…”
Section: Introductionmentioning
confidence: 99%
“…After the SVV outbreaks in Brazil, the virus infection was also reported in different pig categories/herds of other countries of the Americas (Joshi et al., ; Sun, Vannucci, Knutson, Corzo, & Marthaler, ; Xu et al., ) and Asia (Saeng‐Chuto, Rodtian, Temeeyasen, Wegner, & Nilubol, ; Wu et al., ) during 2015 and 2016. However, the number of field reports on SVV‐suspected cases in piglets and SVV diagnostics has decreased in Brazilian pig herds during 2017, suggesting that the infection became endemic in pig herds, leading to asymptomatic and/or subclinical infections.…”
Section: Seneca Valley Virus (Svv) Detection In Biological Samples Comentioning
confidence: 86%